Comparing Innovation and Social Media Strategies in Scandinavian and US Newspapers. Issue 8 (14th September 2018) - Lehtisaari, Katja; Villi, Mikko; Grönlund, Mikko; Lindén, Carl-Gustav; Mierzejewska, Bozena I.; Picard, Robert; Roepnack, Axel
Abstract : The article focuses on innovation and social media strategies in newspaper companies in the US and three Scandinavian countries (Sweden, Norway and Denmark). Many previous studies have focused on the state of journalism and media industry in single countries, although media have distinct features in different countries. Through the comparative setting, it is possible to examine the differences in media innovation strategies and study what factors affect innovation in media production, business models, sources of funding, and social media strategies. The qualitative part of the paper consists of semi-structured in-depth interviews (N = 65) with media managers and experts, which were carried out in Scandinavia in 2016 and in the US in 2017. The quantitative market data covers the years 2006–2016; this timespan corresponds well with the accelerating digital transition in the newspaper business. According to the results, new business models are mostly new combinations of existing revenue streams, while adaptation of new technology is slow, with few exceptions.